Caregiver perceptions of mental health problems and treatment utilisation in siblings of children with mental health problems. (3rd March 2016) - Ma, Nylanda; Furber, Gareth; Roberts, Rachel; Winefield, Helen
Abstract: Background : Siblings of children with mental health problems (MHPs) have been found to have higher rates of psychopathology and impaired psychosocial functioning compared to control children. It is not yet known how these siblings are managed within the clinical service context (e.g. are they assessed for mental health problems? Do they receive appropriate psychological treatment?). Aims : The following brief report describes a pilot study which aimed to explore (a) the rate of caregiver-identified MHPs in siblings and (b) the proportion of siblings receiving psychiatric or psychosocial treatment or support (i.e. treatment utilisation). Methods: Eighty-five caregivers of children receiving treatment at CAMHS were interviewed about the mental health and treatment utilisation of their siblings. Results : The findings revealed a high rate of caregiver-identified MHPs in siblings (34.1%) and a high rate of treatment utilisation (85.7%). Conclusions : The findings suggest that, for the vast majority, when siblings of children with MHPs are identified by their caregivers as having MHPs, they are receiving some kind of support and treatment. Implications for mental health service costs are discussed and recommendations for future research are outlined.